Usage of Innovative Pedagogical Technologies in Teaching Music - Xodjaeva Ziyoda Latipovna (Zien Journals, 2022)
One of the urgent tasks of our time is to educate the younger generation that meets intellectual, high moral and ethical standards, who loves their profession, who is knowledgeable, enthusiastic, professional, exemplary in equipping it with modern innovative pedagogical technologies. The article describes the methods of using innovative technologies "Brainstorm" and "Boomerang", which can be used during the lesson. The teacher-musician educates the younger generation on the basis of such modern technologies as mature, spiritually pure, humane, meeting the requirements of the state and society
Keywords: Innovative pedagogical technologies; brainstorming; mental abilities; handouts